Purchase Intention Model Determined by Tik-Tok Social Media Marketing and Product Knowledge through Price Discount as Intervening Variables - Gatot Wijayanto; Jushemi Jushermi; Sri Wahyuni; Agnes Alvionita; Rahmat Junaidi; Arwinence Pramadewi (Interdiciplinary Journal and Hummanity (INJURITY), 2023)
This study aims to determine the effect of social media marketing on tik-tok and product knowledge on purchase intention which is moderated by price discount on the shopee marketplace in Pekanbaru City. The respondents of this research are those who use the Shopee and Tiktok applications and have shopped online at the Shopee marketplace in Pekanbaru City. The primary data in this study were obtained from distributing questionnaires as an instrument to prove the results of the study and to test the proposed hypothesis. In this study, using the structural equation modeling (SEM) analysis method using Warp-PLS version 6.0 software. Sampling using the technique of Non Probability Sampling with Purposive Sampling procedure by taking a sample of 120 respondents. The results in this study indicate that: 1) Social Media Marketing has a positive and significant effect on Purchase Intention at the Shopee Marketplace in Pekanbaru City, this is evidenced by looking at the pvalue in this study, which is <0.001 with a beta (?) value of 0.380, 2) Product Knowledge has a positive and significant effect on Purchase Intention at the Shopee Marketplace in Pekanbaru City, this is evidenced by looking at the p-value in this study, which is <0.001 with a beta (?) value of 0.352, 3) Social Media Marketing has a positive and positive effect. significantly to Purchase Intention moderated by Price Discount at the Shopee Marketplace in Pekanbaru City, this is evidenced by looking at the p-value in this study, which is <0.001 with a beta () value of 0.280, 4) Product Knowledge has a positive and significant effect on Purchase Intention which is moderated by Price Discount on the Shopee Marketplace in Pekanbaru City, this is proven by by looking at the p-value in this study, which is 0.015 with a beta (?) value of 0.191